(4x+2w-3xy)-(7y+2w-10x)-(3x+2y-4)=

Simple and best practice solution for (4x+2w-3xy)-(7y+2w-10x)-(3x+2y-4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4x+2w-3xy)-(7y+2w-10x)-(3x+2y-4)= equation:


Simplifying
(4x + 2w + -3xy) + -1(7y + 2w + -10x) + -1(3x + 2y + -4) = 0

Reorder the terms:
(2w + 4x + -3xy) + -1(7y + 2w + -10x) + -1(3x + 2y + -4) = 0

Remove parenthesis around (2w + 4x + -3xy)
2w + 4x + -3xy + -1(7y + 2w + -10x) + -1(3x + 2y + -4) = 0

Reorder the terms:
2w + 4x + -3xy + -1(2w + -10x + 7y) + -1(3x + 2y + -4) = 0
2w + 4x + -3xy + (2w * -1 + -10x * -1 + 7y * -1) + -1(3x + 2y + -4) = 0
2w + 4x + -3xy + (-2w + 10x + -7y) + -1(3x + 2y + -4) = 0

Reorder the terms:
2w + 4x + -3xy + -2w + 10x + -7y + -1(-4 + 3x + 2y) = 0
2w + 4x + -3xy + -2w + 10x + -7y + (-4 * -1 + 3x * -1 + 2y * -1) = 0
2w + 4x + -3xy + -2w + 10x + -7y + (4 + -3x + -2y) = 0

Reorder the terms:
4 + 2w + -2w + 4x + 10x + -3x + -3xy + -7y + -2y = 0

Combine like terms: 2w + -2w = 0
4 + 0 + 4x + 10x + -3x + -3xy + -7y + -2y = 0
4 + 4x + 10x + -3x + -3xy + -7y + -2y = 0

Combine like terms: 4x + 10x = 14x
4 + 14x + -3x + -3xy + -7y + -2y = 0

Combine like terms: 14x + -3x = 11x
4 + 11x + -3xy + -7y + -2y = 0

Combine like terms: -7y + -2y = -9y
4 + 11x + -3xy + -9y = 0

Solving
4 + 11x + -3xy + -9y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + 11x + -3xy + -4 + -9y = 0 + -4

Reorder the terms:
4 + -4 + 11x + -3xy + -9y = 0 + -4

Combine like terms: 4 + -4 = 0
0 + 11x + -3xy + -9y = 0 + -4
11x + -3xy + -9y = 0 + -4

Combine like terms: 0 + -4 = -4
11x + -3xy + -9y = -4

Add '9y' to each side of the equation.
11x + -3xy + -9y + 9y = -4 + 9y

Combine like terms: -9y + 9y = 0
11x + -3xy + 0 = -4 + 9y
11x + -3xy = -4 + 9y

Reorder the terms:
4 + 11x + -3xy + -9y = -4 + 9y + 4 + -9y

Reorder the terms:
4 + 11x + -3xy + -9y = -4 + 4 + 9y + -9y

Combine like terms: -4 + 4 = 0
4 + 11x + -3xy + -9y = 0 + 9y + -9y
4 + 11x + -3xy + -9y = 9y + -9y

Combine like terms: 9y + -9y = 0
4 + 11x + -3xy + -9y = 0

The solution to this equation could not be determined.

See similar equations:

| 3x+2y+5x+7y= | | 6sin(x)+9=12 | | -8(6-7v)-7v=-244 | | 6-a+4a=-9 | | 2p-2=16 | | 2.2h=22-6 | | 3p-2=4-3p+6 | | 16x^4+79x^2=2 | | 40+15(x)=205 | | 40+15(9)= | | 40+15(4)= | | n^2+9n*10n+90=30 | | n-8-6=-12 | | 88-26=10(h-6) | | p-26=10(20-6) | | -38-4(15)= | | 7x-34=5y | | p-26=10(18-6) | | -38-4(12)= | | -38-4(6)= | | -a+4a= | | 18+9(x)=288 | | 18+9(24)= | | x^4-9*x^3+27*x^2-91*x=0 | | 45+18= | | -3x-5=-35 | | 4a-a=23 | | x-3y+2z=-28 | | 2(x+3)=14-x | | 5(x-3)=2(4x+1) | | 3(12-x)-6=2 | | -v+3=4 |

Equations solver categories